Influence of planting dates and nitrogen fertilizer levels on grain quality and chemical properties on two Oat varieties (Aveva sativa L.). - El-Sharawy, Aya E.; M. Abdalla, Maha; B Gaballah, Al-Sayed; H. Bassiouny, Ameen (Journal of Neonatal Surgery, 2024)
The field trail was conducted at an extension in Research Farm of Faculty of Technology and Development, Zagazig University at Ghazalah village Zagazig District Sharkia Governorate, Egypt during 2022/2023 and 2023/2024 seasons to study the effect of planting dates (30th October, 15th November and 30th November) and nitrogen fertilizer rates (zero, 30, 60 and 90 kg. N/fed.) on quality and chemical properties of two Oat varieties (White and Rad Oat). The results showed that planting dates had a significant difference in both seasons and combined in all properties, as well as the (30th October) early planting date produced highest germination %, good seedling %, stem length (cm.), root length (cm.), fresh weight of seedling (g.) and dry weight of seedling (g.). While (15th November) middle planting date gave the highest values of chemical properties. Also, the results indicated that White Oat variety was superior and significantly increased than the Red Oat variety in all studied properties of quality and chemical properties. Increasing nitrogen levels from zero,30 to 60 and 90 kg. N/ fed. significantly increased of the most studied characters. In general, 90 kg. N/fed. gave the highest values, followed by 60, 30 kg. N/ fed., while zero treatment was recorded a lowest in this respect. The results indicated also that, grain yield (ton/ fed.) appeared a positive significant correlation with no. grains/panicle, 1000-grain weight (g.), grains protein %, grains carbohydrates %, straw protein% and straw carbohydrates %, germination % and stem length (cm.). In addition, Path analysis revealed that number of spikelets / panicle, number of grains/panicle and 1000-grain weight (g.) were the main grain yield variation and the relative contributions were about 4.985, 5.795 and 126.330 % in respective order. Conclusively, all studied quality characters; 30th October surpassed than 15th November and 30th November, respectively when 90kg. N/fed. gave the highest values viability, vigour and chemical characters. White Oat variety superior in all studied characters, i.e. germination%, good seedling %, stem length (cm.), root length (cm.), fresh and dry weight of seedling (g.), grains protein and carbohydrates %, straw protein and carbohydrates %. The grain yield (ton/fed.) appeared a positive significant correlation with most studied characters..